Banana splits and policy challenges: The ACP Caribbean and the fragmentation of interest coalitions - Clegg, Peter (European Review of Latin American and Caribbean Studies, 2005)
The article considers the changes that have taken place within the political economy of international trade over the last decade. The work begins by assessing briefly the dynamics of the last successful trade negotiations undertaken by the ACP Caribbean – the agreement on a single European banana market in 1993. Since then, however, the international political and economic climate has dramatically changed. The article evaluates recent developments, which have highlighted attention on the political acceptability of trade discrimination, particularly within the context of the General Agreement on Tariffs and Trade and the World Trade Organisation. In addition, there is an analysis of the reform process undertaken by the European Union, both in terms of its membership and policy agenda, which has seriously impacted on Caribbean economic interests. The article establishes that the actors representing the Caribbean were extremely successful in constructing strategic coalitions to defend their trading interests in the early 1990s, but the region must now appreciate that the international environment has changed so dramatically that former negotiating strategies are no longer appropriate. An awareness of the changed negotiating environment on the part of the Caribbean is vitally important if ongoing international trade negotiations are to be completed to the region’s satisfaction. Resumen: Batallas bananeras y desafíos políticos: El grupo ACP del Caribe y la fragmentación de las coaliciones de interésEste trabajo considera los cambios ocurridos en la economía política del comercio internacional durante la última década. El artículo comienza con una breve evaluación de la dinámica de las últimas negociaciones comerciales satisfactorias del grupo ACP del Caribe: el acuerdo sobre un mercado único bananero europeo en 1993. Desde entonces, sin embargo, el clima político y económico internacional ha cambiado drásticamente. El artículo evalúa los recientes acontecimientos que han puesto de relieve la aceptabilidad política de la discriminación comercial, en particular en el contexto del Acuerdo General sobre Tarifas y Comercio y la Organización Mundial del Comercio. Además, se hace un análisis del proceso de reforma efectuado por la Unión Europea, tanto en términos de su ampliación como de su agenda política, los cuales han tenido un grave impacto en los intereses económicos caribeños. El artículo establece que a principios de los años 90 los representantes caribeños tuvieron gran éxito a la hora de desarrollar estrategias para defender sus intereses comerciales, pero en estos momentos la región debe tomar nota de que el ambiente internacional ha cambiado de forma tan radical que las antiguas estrategias de negociación no pueden considerarse ya como apropiadas. Para que la región pueda asegurar un resultado positivo de las actuales negociaciones, es de vital importancia que el Caribe tome conciencia del nuevo clima en que se desarrollan dichas negociaciones.